2019
DOI: 10.1002/adem.201900507
|View full text |Cite
|
Sign up to set email alerts
|

Annealing‐Induced Hardening in Ultrafine‐Grained and Nanocrystalline Materials

Abstract: Annealing of deformed metals is considered as a process necessarily leading to softening due to the annihilation of lattice defects. However, in ultrafine‐grained (UFG) and nanocrystalline materials, annealing at moderate temperatures may induce hardening. This review summarizes those effects that can result in annealing‐induced hardening (AH) in fine‐grained materials. It is noted that only those hardening phenomena are considered as AH effects that are not accompanied by the change of the phase composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…In addition, sample SAA showed a slight strengthening during annealing to 500 K while the crystallite size did not change and the density of lattice defects (dislocations and twin faults) considerably decreased. Similar annealing-induced hardening effect was observed for nanocrystalline Ni and Ni-Mo electrodeposits in some recently published papers [23,[51][52][53][54]. These former studies suggested that annealing at a moderate temperature (at the homologous temperatures of about 0.3-0.4) can yield grain boundary relaxation and segregation of impurities to grain boundaries which retard the deformation processes occurring in the grain boundaries in nanocrystalline materials (e.g., grain boundary sliding).…”
Section: Correlation Between the Microstructure And The Hardness Forsupporting
confidence: 72%
“…In addition, sample SAA showed a slight strengthening during annealing to 500 K while the crystallite size did not change and the density of lattice defects (dislocations and twin faults) considerably decreased. Similar annealing-induced hardening effect was observed for nanocrystalline Ni and Ni-Mo electrodeposits in some recently published papers [23,[51][52][53][54]. These former studies suggested that annealing at a moderate temperature (at the homologous temperatures of about 0.3-0.4) can yield grain boundary relaxation and segregation of impurities to grain boundaries which retard the deformation processes occurring in the grain boundaries in nanocrystalline materials (e.g., grain boundary sliding).…”
Section: Correlation Between the Microstructure And The Hardness Forsupporting
confidence: 72%
“…This effect may be caused by the annihilation of mobile dislocations, and therefore the initiation of the glide of the rest of the dislocations is more difficult during the hardness test. However, this effect can cause only a maximum 20% increase in hardness [42] while in our case the HV 0 was enhanced by a factor of about three (see Figure 7). Therefore, the possible increase in the friction stress cannot be the only reason for the hardening observed after annealing.…”
Section: Discussionmentioning
confidence: 48%
“…Former studies [42] have shown that heat treatments performed at moderate temperatures (at the homologous temperatures 0.35-0.45 × T m , where T m is the melting point) can cause hardening in UFG and nanomaterials. In SPD-processed samples, one possible reason for this anneal hardening is the annihilation of mobile dislocations and/or their clustering, which caused a more difficult initiation of plastic deformation after the heat treatment [42][43][44]. Indeed, in our samples the dislocation density decreased during annealing and, additionally, the dislocation arrangement parameter increased (see Table 2), which suggests significant changes in the dislocation structure.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques yield very hard materials due to the high dislocation density and the small grain size developed during SPD [1,4]. Additional hardening can be achieved by post-SPD annealing due to segregation of solutes to lattice defects (e.g., to dislocations, stacking faults and grain boundaries) [5][6][7][8], annihilation of mobile dislocations [9], rearrangement of the remaining dislocations into harder configurations [10][11][12], clustering of excess vacancies [13,14] and formation of precipitates [15][16][17]. The latter effect is very important in agehardenable materials, such Al-Zn-Mg alloys (7xxx series), where the precipitate structure developed during SPD and subsequent annealing may differ from that formed in coarse-grained counterparts during conventional aging heat treatments.…”
Section: Introductionmentioning
confidence: 99%